The global/local (limited to some regions) effect of cesarean delivery on the risk of pediatric allergic rhinitis: a systematic review and meta-analysis - He, Xingyi; Zhang, Shipeng; Wu, Jiamin; Fu, Qinwei; Zhang, Qinxiu; Peng, Wenyu (Frontiers in Pediatrics, 2023)
Abstract Background—Allergic rhinitis is a chronic and refractory disease that can be precipitated by a variety of factors. Studies have shown an association between caesarean section and the risk of pediatric allergic rhinitis. Methods—The PubMed, Springer, Embase, Cochrane Library, and Web of Science databases were searched to retrieve all studies published from January 2000 to November 2022 and concentrated on the relationship of caesarean section and the risk of pediatric allergic rhinitis. The meta-analysis was conducted to find a correlation between caesarean section and the risk of pediatric allergic rhinitis, and subgroup analysis was performed by region and family history of allergy after adjusting for confounding factors. Pooled odds ratios (ORs) were calculated, publication bias was assessed using the funnel plot, and heterogeneity between study-specific relative risks was taken into account. Results—The results showed that caesarean section was significantly associated with the increased risk of pediatric allergic rhinitis (OR: 1.27, 95%CI: 1.20, 1.35). Subgroup analysis stratified by region indicated that caesarean section increased the risk of pediatric allergic rhinitis, while was the highest in South America (OR: 1.67, 95% CI: 1.10, 2.52), and the lowest in Europe (OR: 1.13, 95% CI: 1.02, 1.25). The results of the subgroup analysis stratified by family history of allergy, indicating that family history of allergy was not associated with the risk of pediatric allergic rhinitis. Conclusion—There is an association between the mode of delivery by caesarean section and the increased risk of pediatric allergic rhinitis, and caesarean section is a risk factor for allergic rhinitis.